Peningkatan Kompetensi Pronunciation Menggunakan Pro Power One - Ivvon Septina Bella; Noviyanti Noviyanti (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2023)
This study was an experimental research which aimed to examine Pro Power One can improve students’ ability and quality of pronunciation in the process of learning English. The research was conducted at Universitas Islam Kebangsaan Indonesia and the subject of the research was 21 students of Informatics Engineering Department Class A, and the data was collected through test. The result of this research showed Pro Power One had proven to improve students’ pronunciation ability and quality. This is supported by the results of the data analysis, which showed an increase in average score of pretest and posttest of 8.75 and 19.65. In addition, the paired samples statistic revealed that the value of Sig. (2- tailed) was 0.00000001 which was lower than the level of significance (α) = 0.05. In other words, learning pronunciation using Pro Power One made a huge improvement.